The Influence Of Prices And Service Quality On Consumer Satisfaction At Minumin Outlets In Bengkulu City - Ermy Wijaya; Yanto Effendi; Ardi indra Permana (Penerbit Jurnal Indonesia, 2023)
The aim of this research is to determine the effect of prices and service quality on consumer satisfaction at Minumin outlets in Bengkulu City. The sample in this study was 120 Minumin consumer respondents in the city of Bengkulu. The data were collected using questionnaires and the analysis method used was multiple linear regression, hypothesis testing. Multiple regression results Y = 0.239-0.203 (X1) + 1.198 (X2) + 0.777. This is proven by the results of the t test, which shows that the calculated t value is -2.674 which is greater than the t table = - 1.980 (- 2.674> -1.980) with a significance level of 0.009 using a limit of 0.05. The significance value is more than 5%, which means Ho is rejected. and Ha accepted. For service quality, the calculated t value was 16,638 which was greater than t table = 1.980 (16.638>1.980) with a significance level of 0.000. By using a significance limit of 0.05, the significant value is smaller than the 5% level, which means Ho is rejected and Ha is accepted. Price (X1) and Service Quality (X2) together have a significant effect on consumer satisfaction (Y) at Minumin outlets in the city of Bengkulu, this is proven by the F test, the Fcount value is 1768.672, then this value will be compared with the Ftable with the level 5% significance shows that Fcount is greater than Ftable (1768.672>3.07) so that Ho is rejected and Ha is accepted..